2018
DOI: 10.2174/1570161116666171226124959
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid is Independently Associated with Diastolic Dysfunction in Apparently Healthy Subjects with Essential Hypertension

Abstract: In hypertensive subjects without HF, UA is independently associated with the presence of DD in both genders and correlates with its severity in women. Further prospective studies are warranted to evaluate the association of UA with adverse cardiovascular outcomes in high-risk populations such as HF with pEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
2
4
0
4
Order By: Relevance
“…Increased diastolic dysfunction and aortic regurgitation were also observed in TAK patients ( Table 3 ). Consistent with the evidence that diastolic dysfunction is associated with increased uric acid levels ( 35 ), a marker of endothelial stress, we found that uric acid levels were significantly elevated in TAK patients with severe aortic regurgitation compared with TAK patients without dysfunction (5.06 ± 1.51/2.96 ± 0.79). Accordingly, TAK patients with moderate-severe aortic regurgitation had elevated uric acid levels compared with patients without regurgitation (6.03 ± 1.22/ 3.64 ± 1.21) or mild-to-moderate diastolic dysfunction (6.03 ± 1.22/3.18 ± 1.20) ( Figure 1A ).…”
Section: Resultssupporting
confidence: 90%
“…Increased diastolic dysfunction and aortic regurgitation were also observed in TAK patients ( Table 3 ). Consistent with the evidence that diastolic dysfunction is associated with increased uric acid levels ( 35 ), a marker of endothelial stress, we found that uric acid levels were significantly elevated in TAK patients with severe aortic regurgitation compared with TAK patients without dysfunction (5.06 ± 1.51/2.96 ± 0.79). Accordingly, TAK patients with moderate-severe aortic regurgitation had elevated uric acid levels compared with patients without regurgitation (6.03 ± 1.22/ 3.64 ± 1.21) or mild-to-moderate diastolic dysfunction (6.03 ± 1.22/3.18 ± 1.20) ( Figure 1A ).…”
Section: Resultssupporting
confidence: 90%
“…Increased diastolic dysfunction and aortic regurgitation were also observed in TAK patients (Table 3). Consistent with the evidence that diastolic dysfunction is associated with increased uric acid levels [26], a marker of endothelial stress, we found that uric acid levels were significantly elevated in TAK patients with severe aortic regurgitation compared with TAK patients without dysfunction (5.06 ± 1.51/2.96 ± 0.79). Accordingly, TAK patients with moderate-severe aortic regurgitation had elevated uric acid levels compared with patients without regurgitation (6.03 ± 1.22/ 3.64 ± 1.21) or mild-to-moderate diastolic dysfunction (6.03 ± 1.22/3.18 ± 1.20) (Figure 1A).…”
Section: Baseline Features and Clinical Differencessupporting
confidence: 89%
“…At the same time, angiotensin receptors can also influence angiotensin type I receptors causing atrial muscle hypertrophy. The accumulation of extracellular matrix proteins leads to obvious fibrosis of the atria, which affects conduction function and triggers atrial remodeling (22,23).…”
Section: Discussionmentioning
confidence: 99%